ОСНОВНІ ТЕНДЕНЦІЇ СТАНОВЛЕННЯ ТА РОЗВИТКУ МЕТОДИКИ НАВЧАННЯ ЛІТЕРАТУРИ В ШКОЛІ РАДЯНСЬКОГО ПЕРІОДУ (20–30 РР. ХХ СТ.) - Яценко, Таміла (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розкриваються умови і напрям и становлення української методики навчання літератури у контексті освітніх завдань радянської загальноосвітньої школи 20–30 рр. ХХ століття. Характеризуються основні тенденції розвитку літературної освіти, що помітно позначилися на формуванні методичної думки. Акцентується на проблемі інтелектуалізації навчального процесу, значенні самостійної пізнавальної діяльності учнів, пошуку інноваційних форм навчання, посиленні його виховної ролі та домінуванні педологічних ідей в аспекті актуалізації психологічного компоненту освіти. Стверджується культурологічна спрямованість літературної освіти, встановлюється взаємозв’язок змісту і форм шкільної освіти, що забезпечує успішність роботи вчителя й учнів на уроці літератури. Автор акцентує на одній із позитивних тенденцій шкільної освіти та виховання означеного періоду як ефективній передумові розвитку сучасної літературної освіти щодо формування компетентного учня-читача та виховання свідомого громадянина. В статье раскрываются условия и направления становления украинской методики преподавания литературы в контексте образовательных целей советской общеобразовательной школы 20–30 гг. ХХ века. Характеризуются основные тенденции развития литературного образования, которые способствовали формированию и развитию методики как науки. Акцентируется на проблеме интеллектуализации учебного процесса, значении самостоятельной познавательной деятельности учеников, поиске инновационных форм обучения, усиления его воспитательной роли и доминирования идей педологии в аспекте актуализацией психологического компонента образования. Аргументируется культурологическая направленность литературного образования, обосновывается взаимосвязь содержания и форм школьного образования, что обеспечивает успешность работы учителя и учеников на уроке литературы. Автор акцентирует на одной из позитивных тенденций школьного образования и воспитания анализируемого периода как предпосылке эффективного современного литературного образования и формирования компетентного ученика-читателя и воспитания сознательного гражданина. In this article the methodical properties and ways of Ukrainian literature teaching methodology development in context of educational issues of Soviet Union school in 20-30th of the XX centuries is considered. The main trends in literature education development that are influenced on methodical thought formation are characterised. The intellectualisation of educational process, the new study forms search, the increase of its educative part and pedagogical ideas domination in connection of psychological educational component actualisation is emphasised. The cultural direction of literature education is confirmed; the interaction of content and ways of school education that provide teacher’s and student’s work success at the literature lesson is established. The positive trends of school literature educational practise development such as native language education, educational orientation on student’s personal self-education, the student’s not only knowledge formation but also tries of educational system decentralisation etc. are distinguished. The general trend of illustrative literature teaching at school is negative evaluated. The author emphasised that positive teaching trends and training of indicated period became successful conditions of effective literature education and competent reader and citizen education of the second part of ХХ – beginning of ХХI centuries.